Clinical and systems of care factors contributing to individual patient decision-making for early mobilization post-stroke - Rethnam, Venesha; Hayward, Kathryn S.; Johns, Hannah; Carvalho, Lilian B.; Churilov, Leonid; Bernhardt, Julie (Frontiers in Stroke, 2023)
Introduction Many stroke guidelines recommend against starting intensive out-of-bed activity (mobilization) within 24 h post-stroke. Few guidelines address care after the first 24–48 h, and little information is provided about how early mobilization decisions should be tailored to patients. We aimed to identify clinical and systems of care factors contributing to individual patient decision-making for early mobilization post-stroke. Methods Expert stroke clinicians were recruited to participate in an interactive one-on-one session that included an introductory semi-structured interview followed by an assisted data exploration session using an early mobilization data visualization tool. Results Thirty expert stroke clinicians with a median (interquartile range) 14 (10–25) years of experience were included. Stroke type and severity, and medical stability were identified as important clinical decision-making factors by the majority of expert stroke clinicians. Inadequate staffing and equipment were frequently indicated as barriers to early mobilization. The perceived characteristics of early mobilization responders were mild or moderate stroke severity, ischemic stroke, partial anterior circulation stroke, younger age, and one or fewer comorbidities. Perceived characteristics of early mobilization non-responders included severe stroke severity, hemorrhagic stroke, total anterior circulation stroke, older age, those with persistent vessel occlusion or high-grade stenosis, hemodynamic instability, multimorbidity and an altered state of consciousness. Some characteristics led to uncertainty amongst interviewees e.g., early mobilization decision-making were moderate stroke severity, older patients, and those with lacunar circulation infarcts. Discussion We gained unique, in-depth insights into patient and systems of care factors that contribute to individual patient decision-making related to early mobilization post-stroke. The identified areas would benefit from further empirical research to develop structured decision support for clinicians.